2015
DOI: 10.1159/000375479
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of Disease Severity but Not Actionability Correlate with Interest in Receiving Genomic Results: Nonalignment with Current Trends in Practice

Abstract: Purpose: Frameworks highlighting disease actionability and severity are evolving to address the need to organize results from genome-wide analyses. This approach represents a paradigm shift from consultations focused on one or more genes to multiple genes for multiple disorders. Empirical input from the general population is lacking, yet seems essential for understanding how to maximize patient autonomy and satisfaction in the decision-making process. Methods: We conducted a cross-sectional online survey with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 25 publications
6
26
0
Order By: Relevance
“…Multiple studies have documented that most participants want most, and usually all, possible secondary findings. This trend is consistent between studies asking this question as a hypothetical [29][30][31][32][33] or to inform actual return of results [34][35][36][37] . Consistent with these previous studies, the vast majority (84.8%) of parents participating in our study chose to receive all 13 categories of potential secondary results.…”
Section: Patient Preferencessupporting
confidence: 71%
“…Multiple studies have documented that most participants want most, and usually all, possible secondary findings. This trend is consistent between studies asking this question as a hypothetical [29][30][31][32][33] or to inform actual return of results [34][35][36][37] . Consistent with these previous studies, the vast majority (84.8%) of parents participating in our study chose to receive all 13 categories of potential secondary results.…”
Section: Patient Preferencessupporting
confidence: 71%
“…Although our study uniquely addressed the issue of who should decide, our findings are supported by other findings that people, regardless of their health status, would generally like a choice about the WGS information they receive and many clinicians believe that people should have a choice about the results they receive (actionable or not). 1719,29 Concerns have been raised regarding the feasibility of sharing WGS results, specifically with regard to the large amount of time and resources required to review and discuss all possible results in a genomic report, 30,31 as well as the difficulty counselling patients about all results in a report, or choosing a subset of actionable genes for analysis, when this information is constantly evolving. 7 These are important considerations given that the general population has limited knowledge and understanding of personalized medicine 32 and genomic policy experts have raised concerns regarding genomic literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Graves et al () investigated the association between disease severity and actionability and found dementia had the largest percentage of high‐severity ratings, followed by adult blindness and breast/ovarian cancer. Similarly, in the present study, Alzheimer's disease had the greatest percentage of high‐severity ratings.…”
Section: Discussionmentioning
confidence: 99%
“…The three conditions were chosen to represent different types of WGS results that could occur, as well as conditions that differ in severity: Alzheimer's disease is incurable, lethal, and generally later onset (Thies & Bleiler, 2011); macular degeneration is incurable, not lethal, and generally later onset (de Jong, 2006); colon cancer is generally detectable early, treatable, lethal if untreated, and sometimes occurs with an earlier onset (Jasperson, Tuohy, Neklason, & Burt, 2010). While Alzheimer's disease and macular degeneration do not meet ACMG criteria for reporting of secondary findings, these conditions are identifiable through WGS, and they are comparable to three used by Graves et al (2015) (i.e., dementia, adult blindness, and breast/ovarian cancer);…”
Section: Sample and Proceduresmentioning
confidence: 99%